Measuring the factors impact on firm performance recovery in coffee chain in Vietnam - Pham, Manh Tien (Asian Journal of Economic Modelling, 2024)
This paper examines the relationship between customer satisfaction antecedents and firm performance recovery in the coffee chain in Vietnam and suggests suitable solutions for those firms to increase firm performance. The booming development period of food and beverage industry, especially coffee chains in Vietnam, also creates fierce competition for these companies, particularly in attracting potential customers and keeping current buyers. In this research, the dependent variables are service recovery performance, the customer satisfaction antecedents, including customer loyalty (service quality, perceived price fairness, and customer satisfaction), technology adoption, and flexibility. To achieve this purpose, a quantitative research design was developed, involving data collection from more than 300 customers who have used services from outstanding coffee chains in Vietnam through a structured questionnaire. The collected data underwent rigorous analysis via the Structural Equation Model, confirming the construct’s validity, reliability, and discriminant validity. The results show that customer loyalty was significantly and positively impacted by customer satisfaction and perceived price fairness. Further, technology adoption and flexibility positively influenced firm performance recovery. However, the research does not find out the relationship between service quality and customer loyalty. The findings highlight the solutions for coffee chains in Vietnam to increase firm performance during the difficult market conditions, natural disasters, and epidemic periods.